(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article analyzes issues related to the accuracy of spatial data in digital cartography and Geographic Information Systems (GIS). The inconsistency of coordinate systems, projection errors, discrepancies in data integration, and the human factor are considered as the main problems. In addition, the importance of transformation algorithms, standardization, and data quality control mechanisms is highlighted. The research findings are aimed at developing scientific and practical recommendations to improve accuracy and ensure data reliability in GIS systems